Initial Insights Into the Genetic Epidemiology of SARS-CoV-2 Isolates From Kerala Suggest Local Spread From Limited Introductions - Radhakrishnan, Chandni; Divakar, Mohit Kumar; Jain, Abhinav; Viswanathan, Prasanth; Bhoyar, Rahul C.; Jolly, Bani; Imran, Mohamed; Sharma, Disha; Rophina, Mercy; Ranjan, Gyan; Sehgal, Paras; Jose, Beena Philomina; et al. (Frontiers in Genetics, 2021)
Coronavirus disease 2019 (COVID-19) rapidly spread from a city in China to almost every country in the world, affecting millions of individuals. The rapid increase in the COVID-19 cases in the state of Kerala in India has necessitated the understanding of SARS-CoV-2 genetic epidemiology. We sequenced 200 samples from patients in Kerala using COVIDSeq protocol amplicon-based sequencing. The analysis identified 166 high-quality single nucleotide variants encompassing 4 novel variants and 89 new variants in the Indian isolated SARS-CoV-2. Phylogenetic and haplotype analysis revealed that the virus was dominated by three distinct introductions followed by local spread suggesting recent outbreaks and belongs to A2a clade. Further analysis of the functional variants revealed two variants in the S gene associated with increased infectivity and 5 variants mapped in primer binding sites affects the efficacy of RT-PCR. To the best of our knowledge, this is the first and most comprehensive report of SARS-CoV-2 genetic epidemiology from Kerala.